2017
DOI: 10.1146/annurev-publhealth-031816-044528
|View full text |Cite
|
Sign up to set email alerts
|

An Appraisal of Social Network Theory and Analysis as Applied to Public Health: Challenges and Opportunities

Abstract: The use of social network theory and analysis methods as applied to public health has expanded greatly in the past decade, yielding a significant academic literature that spans almost every conceivable health issue. This review identifies several important theoretical challenges that confront the field but also provides opportunities for new research. These challenges include (a) measuring network influences, (b) identifying appropriate influence mechanisms, (c) the impact of social media and computerized comm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
120
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 147 publications
(130 citation statements)
references
References 81 publications
7
120
0
3
Order By: Relevance
“…The general concept of a network is based on interconnectivity between different components and their interdependencies to explain an outcome. The most known and representative examples of this concept are social networks . In biology, the same concept, called network biology, can be applied, connecting several entities at the molecular, cellular, pathways or more complex levels to decipher a phenotype, a disease, or any kind of biological outcome of interest.…”
Section: Network‐based Conceptmentioning
confidence: 99%
“…The general concept of a network is based on interconnectivity between different components and their interdependencies to explain an outcome. The most known and representative examples of this concept are social networks . In biology, the same concept, called network biology, can be applied, connecting several entities at the molecular, cellular, pathways or more complex levels to decipher a phenotype, a disease, or any kind of biological outcome of interest.…”
Section: Network‐based Conceptmentioning
confidence: 99%
“…For example, a simple measure of the presence of a family “kin keeper,” a go-to person in the family who is most knowledgeable about family health, could give insight into how family characteristics affect views about the importance of FHH [87-89]. Further, other innovative data collection techniques such as respondent-driven sampling and network-based approaches in dissemination campaigns could lend insight into factors that improve engagement of families in FHH assessment [90, 91]. Strategies to improve FHH collection also could draw on communal coping theory that suggests families may be galvanized around perceptions of shared risk and responsibility for health [92].…”
Section: Discussionmentioning
confidence: 99%
“…Empirical evidence in other domains supports the value of network diagnostics in inducing behavior change. Network processes have been found to mediate or moderate the effectiveness of a wide range of health interventions (Valente and Pitts 2017). A randomized controlled trial (RCT) showed that targeting the most influential (most popular/best leaders) peers in the classroom stimulated peer influence on children's own increased water consumption (Smit et al 2016).…”
Section: Network Diagnostics To Recognize and Reduce Victimizationmentioning
confidence: 99%
“…Therefore, interventions are tailored to the particular situation (Cunningham et al 2019;Saarento et al 2015). Multiple studies have shown that network diagnostics can be used effectively in practice to reduce other health problems (for an overview, see Valente and Pitts 2017). Moreover, research has demonstrated that relationship information can be valuable to explain bullying processes (e.g., Sainio et al 2011;Van Der Ploeg et al 2020).…”
mentioning
confidence: 99%